Frequency and clinicopathologic associations of microsatellite instability and PD-L1 expression in Vietnamese patients with gastric cancer - Van Thinh, Pham; Ngoc Dung, Tran; Thuat Thang, Vi; Thanh Chung, Nguyen; Thuy Linh, Nguyen; Thu Hien, Nguyen; Dinh Tien, Truong; Son Tung, Dang; Thai Tra, Dang; Mai Hanh, Nguyen; Van Khuong, Kieu; Xuan Huy, Pham; et al. (Trends in Immunotherapy, 2023)
Background: Our study aimed to determine the frequency of microsatellite instability (MSI) and characterize the associations between MSI status, PD-L1 expression, and clinicopathological features in Vietnamese patients with gastric cancer. Methods: We performed a retrospective cohort study that analyzed 87 patients with gastric cancer who underwent gastrectomy from January 2020 to March 2023. MSI status was assessed by immunohistochemistry for mismatch repair proteins. PD-L1 expression was evaluated by tumor proportion score (TPS) and combined positive score (CPS). Associations between MSI, PD-L1, and clinicopathologic factors were analyzed. Results: MSI-high (MSI-H) was identified in 13.8% of tumors and significantly associated with intestinal subtype, moderate differentiation, necrosis, tumor-infiltrating lymphocytes, and PD-L1 positivity. Lymphatic invasion correlated with increased TPS. Intestinal classification correlated with higher CPS. Conclusion: MSI-H identifies a subset of gastric cancers with distinct features. PD-L1 expression is associated with aggressive disease parameters. Biomarker-based stratification may guide personalized therapy.